Mediating effect of social support on the relationship between resilience and burden in caregivers of people with dementia. (January 2020) - Ruisoto, Pablo; Contador, Israel; Fernández-Calvo, Bernardino; Serra, Lídia; Jenaro, Cristina; Flores, Noelia; Ramos, Francisco; Rivera-Navarro, Jesús
Highlights: Resilience and social support protect family caregivers of people with dementia against burden. The protective effect remained robust after controlling for sociodemographic and clinical covariates. Social support moderated the protective effect of resilience over burden. Abstract: Objective: This study examined different predictive factors of burden in a sample of family caregivers of patients with dementia (PWD). In particular, the influence of social support and resilience on burden was tested, considering potential mediation effects. Methods: A total of 283 primary and family caregivers in Spain were evaluated using a standardized protocol to assess sociodemographic characteristics, clinical state of PWD and specific variables of caregiving and care providers. Results: The role of caregiver of PWD was more common in women, reporting significantly higher levels of burden than men. Resilience and social support accounted for most of the variance in burden. Furthermore, social support partially mediated the relationship between resilience and burden in caregivers. Conclusions: Caregivers' resilience and social support are protective factors against burden in caregivers of PWD. Both factors should be considered for tailored interventions aimed at reducing the health costs of burden in this population.